HADHANAHDALAM PERSPEKTIF HUKUM KELUARGA ISLAM - Nuryanto, Nuryanto (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2014)
Hadanah is widely known as children upbringing conducted by the parents. It involves parentsâ activities of educating and serving the children. This research deals with hadanah seen from Islamic family law. The objective of the research was to clarify whether hadanah should be accounted as a right or an obligation for the children. This article is a library research in nature with a descriptive qualitative method. The research data was analyzed through the so-termed content analysis. The research approach used in this research was normative theological so that the result or the finding of the research could be accepted normatively. The result of the research shows that hadanah is a right that belongs to a mother, father, and child. When a dispute occurs, the childâs right should be a priority from which the solution is derived. This research suggests that the parents should understand and elaborate the concept of hadanah into modern context.Keywords:Child upbringing, child, parents